HUBUNGAN KECERDASAN EMOSIONAL DENGAN PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TK CENDANA RUMBAI PESISIR KOTA PEKANBARU - Novia Annesha Wulandari; Zulkifli Zulkifli; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study aims to determine the level of association between emotional intelligence and the moral behavior of children aged 5-6 years at the TK Cendana Rumbai Pesisir Pekanbaru. The samples in this study numbered 63 children. The method used in this study is a quantitative correlation to see the relationship between the free variables by binding. The data collection techniques used are by observation. Data analysis techniques Use the Person Product moment correlation test with the IBM SPSS for Windows Ver. 23 program. From the research results known levels of emotional intelligence are in the category enough with a percentage value of 69.26% and the level of moral behavior of the child is in the category is sufficient with a percentage value of 66.07%. Based on the hypothesis test results obtained there is a positive and significant relationship between emotional intelligence to the moral behavior of children aged 5-6 years in TK Cendana Rumbai coastal city of Pekanbaru. This can be noted from the value of the correlation coefficient of rxy = 0.665 and the value of the coefficient of determination resulting in KD = R ² x 100% = 44.20% has the meaning that emotional intelligence affects a 44.20% of moral behavior. Key Words: Emotional Intelligence, Moral Behavior